A Digest of the Laws of the State of Florida: From the Year One Thousand Eight Hundred and Twenty-Two, to the Eleventh Day of March, One Thousand Eight Hundred and Eighty-One, Inclusive, at 403 (James F. McClellan ed.,1881) - (:unkn) unknown (My University, 1868)
Offences Against Public Peace, § 13 (Fla. Act of Aug. 6, 1868, ch. 1637): Prohibited the carrying "about or on their person" any dirk, pistol or other arm or weapon, except a "common pocket knife." Punishable by fine up to $100 or imprisonment up to 6 months.
Keywords: CARRY